(untitled) (Journal of EAHIL, 2020)
This article describes the development of the learning environment in the library at Karolinska Institute. It all began with a university-wide project, but when taking into consideration what makes a library special, the librarians had to find their own application of the pedagogical thoughts behind the project. The students’ needs are changing depending on situations and times, so the library environment needs to be flexible and regularly updated accordingly.